2008
DOI: 10.1136/ard.2007.075101
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb enthesopathy in patients with psoriasis without clinical signs of arthropathy: a hospital-based case-control study

Abstract: Background: Psoriasis is associated with a form of spondyloarthropathy in 10-30% of cases. A major feature of psoriatic arthritis is enthesitis. In some patients with psoriasis the presence of enthesitis could be underdiagnosed. Objective: To investigate the presence of lower limbs entheseal abnormalities in patients with chronic plaque psoriasis without signs and symptoms of psoriatic arthritis. Methods: Thirty patients with psoriasis and 30 controls underwent ultrasonographic evaluation of Achilles, quadrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
189
1
14

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(228 citation statements)
references
References 21 publications
24
189
1
14
Order By: Relevance
“…Gisondi et al have used ultrasound to assess entheses in psoriasis patients, showing a significantly higher mean GUESS score compared to controls with other types of skin disease (14). Scarpa et al examined early PsA subjects (with and without psoriasis) with articular and/or entheseal involvement of 12 weeks or less duration and showed that bone scintigraphy identifies 3 times as many affected areas as CE.…”
Section: Discussionmentioning
confidence: 99%
“…Gisondi et al have used ultrasound to assess entheses in psoriasis patients, showing a significantly higher mean GUESS score compared to controls with other types of skin disease (14). Scarpa et al examined early PsA subjects (with and without psoriasis) with articular and/or entheseal involvement of 12 weeks or less duration and showed that bone scintigraphy identifies 3 times as many affected areas as CE.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 30 patients originally evaluated 5 , 28 returned for a re-evaluation. No patient received systemic treatment with a disease-modifying antirheumatic drug.…”
Section: To the Editormentioning
confidence: 99%
“…We previously used ultrasound (US) to show a high frequency of subclinical entheseal involvement in patients presenting with psoriasis but without clinically evident arthritis 5 . We investigated whether subclinical enthesopathy in patients with psoriasis predicted the future development of PsA.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The most impressive aspect of US in the assessment of enthesopathy is the wide range of both grayscale and power Doppler (PD) patterns even in patients with early or subclinical disease 13,14 .…”
Section: The Sound Of Enthesismentioning
confidence: 99%